ANALISIS KONFLIK SOSIAL DALAM NOVEL SI ANAK BADAI KARYA TERE LIYE : KAJIAN SOSIOLOGI SASTRA - Maguna Eliastuti; Ana Triyana; Fachri Aulia; Fathia Fidzri Aulia; Nur Amaliyah (Bajang Institute, 2023)
The study entitled